Pembuatan Etanol dari Buah Salak (Salacca zalacca) Melalui Proses Fermentasi - Wartini, Ni Ketut; Abram, Paulus Hengky; Rahman, Nurdin (Jurnal Akademika Kimia, 2017)
The study aimed to determine the level of ethanol that produced by the flesh of salak fruits with the fermentation process. The method used was an experimental method. The technical is fermentation, with tape yeast starter, determination of ethanol and purification. Ethanol level in the flesh of fresh fruits without handling was 11.3%, the highest levels of ethanol in the fruit flesh of 4 days after the plucking was 7.6%, and the fruit flesh of 7 days after the plucking was 3.4%.Â